2018
DOI: 10.1371/journal.pone.0204569
|View full text |Cite
|
Sign up to set email alerts
|

Managers, modelers, and measuring the impact of species distribution model uncertainty on marine zoning decisions

Abstract: Marine managers routinely use spatial data to make decisions about their marine environment. Uncertainty associated with this spatial data can have profound impacts on these management decisions and their projected outcomes. Recent advances in modeling techniques, including species distribution models (SDMs), make it easier to generate continuous maps showing the uncertainty associated with spatial predictions and maps. However, SDM predictions and maps can be complex and nuanced. This complexity makes their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…New research is continually improving the understanding of the responses of species to climate change, but this knowledge can often be inadequate because the predictions of future impacts are fraught with uncertainty (Pearson, 2006). It is crucial that the uncertainty associated with predicted species distribution data is summarized and visualized in order to guide conservation plans (Wilson, 2010; Guisan et al, 2013; Costa, Kendall & McKagan, 2018). In this study, the variance arising from ENMs was identified as the main cause of distortion in the predictions; thus, the choice for a specific ENM in modelling decisions markedly contributes more to bias than the choice of climate models or emission scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…New research is continually improving the understanding of the responses of species to climate change, but this knowledge can often be inadequate because the predictions of future impacts are fraught with uncertainty (Pearson, 2006). It is crucial that the uncertainty associated with predicted species distribution data is summarized and visualized in order to guide conservation plans (Wilson, 2010; Guisan et al, 2013; Costa, Kendall & McKagan, 2018). In this study, the variance arising from ENMs was identified as the main cause of distortion in the predictions; thus, the choice for a specific ENM in modelling decisions markedly contributes more to bias than the choice of climate models or emission scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…They even have potential to inform new proposed workflows for the IUCN Green Status of Species, which measures the success of a species conservation plan and the potential for recovery (Grace et al, 2021). Because of this, uncertainty related to SDMs should be better communicated to decision makers in a meaningful and informative way (Costa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%